2013
DOI: 10.1371/journal.pone.0083857
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Gamma Release Assay Performance of Pleural Fluid and Peripheral Blood in Pleural Tuberculosis

Abstract: BackgroundThe diagnosis of pleural tuberculosis (TB) remains to be difficult. Interferon-gamma release assay (IGRA) is a promising method for diagnosing TB in low TB burden countries. The release of interferon-gamma (IFN-γ) by T lymphocytes increases at a localized site of infection with Mycobacterium tuberculosis antigen. This study aimed to examine the clinical accuracy of T-SPOT.TB on pleural fluid and peripheral blood for the diagnosis of pleural TB in high TB burden country.Methods168 subjects with pleura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…The full text of the remaining 10 articles was examined, and one study (Losi et al, 2010) was excluded because it did not use the t-spot assay format. The final meta-analysis therefore included nine publications (Losi et al, 2007;Lee et al, 2009;Dheda et al, 2009;Kang et al, 2012;Keng et al, 2013;Liao et al, 2014;Zhang et al, 2014;Liu et al, 2013Liu et al, , 2014 TN = truly negative result; TP = truly positive result; FN = false-negative result; FP = false-positive result. a Enzymelinked immunospot assay (T-SPOT-TB; Oxford Immunotec Ltd., Oxford, UK) measuring the immune response to an ESAT-6 or CFP-10 peptide.…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the remaining 10 articles was examined, and one study (Losi et al, 2010) was excluded because it did not use the t-spot assay format. The final meta-analysis therefore included nine publications (Losi et al, 2007;Lee et al, 2009;Dheda et al, 2009;Kang et al, 2012;Keng et al, 2013;Liao et al, 2014;Zhang et al, 2014;Liu et al, 2013Liu et al, , 2014 TN = truly negative result; TP = truly positive result; FN = false-negative result; FP = false-positive result. a Enzymelinked immunospot assay (T-SPOT-TB; Oxford Immunotec Ltd., Oxford, UK) measuring the immune response to an ESAT-6 or CFP-10 peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the shortage of available methods for diagnosis of TB, IGRAs have increasingly been used as an auxiliary diagnostic tool for active TB in clinical practice in China (18,(31)(32)(33). Indeed, it has been reported that detection of IFN-␥ in pleural fluid mononuclear cells is useful for diagnosis of tuberculous pleurisy (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that detection of IFN-␥ in pleural fluid mononuclear cells is useful for diagnosis of tuberculous pleurisy (31,32). Additionally, IGRAs have improved the sensitivity for diagnosis of pulmonary TB (18), pediatric TB (34), and osteoarticular TB (33).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of IFN-␥ is a strong indicator of M. tuberculosis infection, but the value of IGRAs for the diagnosis of TP is still controversial. Some studies show that IGRAs are useful for TP diagnosis even in areas where TB is highly endemic (10,11). However, other studies show that assays for the detection of adenosine deaminase and IFN-␥ are superior to IGRAs and do not recommend the use of IGRAs for TP diagnosis (12)(13)(14)(15).…”
mentioning
confidence: 99%